Teachers’ Perceptions of the Role of Project-Based Learning in Developing English-Speaking Skills - Rendi Dwi Putra; Margana; Elis Susanti (ENGLISH FRANCA : Academic Journal of English Language and Education, 2026)
This study aims to explore teachers' perceptions of the implementation of Project-Based Learning in teaching English speaking skills at the Senior High School level. This study used a descriptive qualitative approach involving five English teachers at SMA Negeri 3 Kotabumi as participants. Data were collected through in-depth interviews to gain a comprehensive understanding of teachers' experiences, perspectives, and strategies during the implementation of PjBL. The results of the study indicate that PjBL can improve learning effectiveness by strengthening students' confidence in public speaking, creating a more communicative learning environment, and encouraging productive teamwork. Teachers also emphasized that the implementation of PjBL allows students to use English in authentic contexts, thus optimally developing their communication skills. In addition, some teachers have begun to shift the focus of assessment from language structure to aspects of fluency, eloquence, and clarity of communication. However, challenges such as limited time, facilities, and differences in student abilities remain, forcing teachers to implement flexible and adaptive strategies in project planning and implementation. These findings have significant implications for teacher training, curriculum development, and educational policies that support 21st-century skills-based learning.